2011
DOI: 10.1186/1556-276x-6-268
|View full text |Cite
|
Sign up to set email alerts
|

Excitonic effects on the second-order nonlinear optical properties of semi-spherical quantum dots

Abstract: We study the excitonic effects on the second-order nonlinear optical properties of semi-spherical quantum dots considering, on the same footing, the confinement potential of the electron-hole pair and the Coulomb interaction between them. The exciton is confined in a semi-spherical geometry by means of a three-dimensional semi-parabolic potential. We calculate the optical rectification and second harmonic generation coefficients for two different values of the confinement frequency based on the numerically com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(10 citation statements)
references
References 13 publications
(25 reference statements)
0
10
0
Order By: Relevance
“…4,20 The nonlinear optical properties are reported for different forms of ZnO such as single crystals, thin films, nanowires and nano-ribbons. 14 The enhancement of the nonlinear optical properties as compared to bulk counterpart is observed for thin films. 30 ZnO owing to its non-centrosymmetric uniaxial crystal structure possesses second order nonlinear coefficient of the order of 10 −12 m/V.…”
Section: Introductionmentioning
confidence: 82%
See 2 more Smart Citations
“…4,20 The nonlinear optical properties are reported for different forms of ZnO such as single crystals, thin films, nanowires and nano-ribbons. 14 The enhancement of the nonlinear optical properties as compared to bulk counterpart is observed for thin films. 30 ZnO owing to its non-centrosymmetric uniaxial crystal structure possesses second order nonlinear coefficient of the order of 10 −12 m/V.…”
Section: Introductionmentioning
confidence: 82%
“…Since the first observation of the SHG 9 several studies are reported on the materials with large second order nonlinearity. 8,[10][11][12][13][14][15][16][17][18][19] The second order nonlinear optical properties in semiconductor nanostructures associated with the interband transitions (between the levels of different bands) and the intraband transitions (between levels of the same band) have been studied by several authors. 8,20,21 The second order nonlinearity has potential applications such as in harmonic generation, biological imaging, and nonlinear optical microscopy.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Some of the previous works make an approximation about the shape of the dot. Some take it as onedimensional [7,13,17], two-dimensional [8,16], disk-like [10,11,15], or semi-spherical [9]. This may simplify the calculation of the electronic structure of the QD.…”
Section: Introductionmentioning
confidence: 98%
“…There have been a number of investigations of the problem of exciton-related nonlinear optical properties of a QD [7][8][9][10][11][12][13][14][15][16][17][18][19][20]. The majority of these works are either numerical or considering only the strong confinement limit.…”
Section: Introductionmentioning
confidence: 99%